ab initio Structural, Electronic and Vibrational Properties of GaSb Nanocrystals Using Diamondoids and Large Unit Cell Method - Ahmed Abdulsattar, Mudar; M. Mohamad, Majed (Asian Journal of Chemistry, 2015)
GaSb diamondoids and large unit cell method are used as building blocks to investigate size dependence of electronic properties of GaSb nanocrystals. Density functional theory is used combined with large unit cell and diamondoids structures. GaSbH6 and Ga3Sb3H12 molecules and GaSb diamondoids that include GaSb-diamantane, GaSb-tetramantane and GaSb-hexamantane are investigated in addition to 8, 16, 54 and 64 atoms large unit cells. Results show that energy gap generally decreases with shape fluctuations as the number of atoms increases and eventually stabilizes and gradually increases for the number of atoms greater than 200 atoms. Bond lengths and tetrahedral angles of diamondoids show that these molecules are very close to ideal zinc blende structure. Bond lengths encounter an expansion near the surface of diamondoids. Variation with size of some of the vibrational lines that include the radial breathing mode, highest force constant mode, Ga-H symmetric vibrations and Sb-H asymmetric vibrations is shown. A comparison with experiment reveals the good results that can be obtained from present theory.